The role of selenium in the pathogenesis of thyroid disease - Ekaterina A. Troshina; Evgeniya S. Senyushkina; Maria A. Terekhova (Клиническая и экспериментальная тиреоидология, 2019)
The past few years have been actively discussing the role of individual macro- and micronutrients as factors regulating the functional activity of organs and systems and reducing the risk of developing a number of diseases, including thyroid diseases.